Perkembangan Sejarah Bahasa Indonesia Sebelum Merdeka - Juniarti, Livia Via; Repelita, Tridays; Nandini, Imelda Nova; Ramadhan, Gilang (Jurnal Ilmiah Wahana Pendidikan, 2025)
Malay constitue l'une des langues les plus utilisées en Indonesia and is the basis of the Indonesian language, which is recognized in the Youth Pledge, making it the first language to become the state language and national language. The Indonesian language comes from the Riau Malay language. Historical sources show that the use of the Riau Malay language was already used during the Malayu and Srivijaya kingdoms. For 81 years (1928–2009), the Indonesian language also went through three stages, namely as a language of unity, comme la langue officielle du pays, and as an international languageThe purpose of writing this junal is to acquire une compréhension de l'histoire de the Indonesian language and its place in Indonesia. Cette étude a été réalisée en utilisant une méthode descriptive qualitative avec le type de literature Recherche. Selon les résultats de la recherche, Malay was the first language used in interethnic conversations before Indonesian. Indonesian functions comme langue de communication, langue d'union, langue de l'État et langue nationale in four ways.